EFEKTIVITAS PENERAPAN RUANG HENTI KHUSUS (RHK) DI PERSIMPANGAN JALAN PERKOTAAN (Studi Kasus: Persimpangan Jalan Pasteur-Pasirkaliki Kota Bandung) - Sri Amelia; Mrs. Juanita (Universitas Muhammadiyah Purwokerto, 2011)
Population growth since the post-crisis motorcycle Indonesia Economic in mid-1998 showed a new phenomenon. This is expected to affect traffic characteristics, which in turn can degrade the performance of estimated traffic infrastructure. Insert motorcycle moves forward through the gaps between the rows of cars queuing up to reach the stop line. Buildup that occurs even in general irregular and also violated the traffic rules as beyond the stop line, close the left turn traffic movement and prevents direct flow of pedestrians. One form of treatment is the provision of bike facilities in the form of a special stopping space facility (RHK) to motorcycles at urban crossroads. One way to examine the effectiveness of the implementation of RHK motorcycle is to assess the performance of traffic (flow) at the foot of the intersection. Results of analysis are before and after implementation of a motorcycle RHK (before, after 1 and after 2) shows that there is increase in the average number of vehicles at peak times up to 13% in the city of Bandung. Studies using the method of calculating the traffic flow MKJI 1997, RHK obtained results that the application of motorcycles in urban crossroads affect the current to increase the average vehicle to reach more than 10%. Key-word: proportion of motorcycles, motorcycle specific stopping space, traffic performance